STRATEGI KOMUNIKASI TERHADAP KEPUTUSAN KUNJUNGAN KONSUMEN DI VILLAGE FUTSAL JALAN KAMPUNG SUSUK MEDAN - Christian Haposan Simanjuntak (Jurnal Niaga & Bisnis (e-journal), 2014)
The aim of this research is to find out forms a strategy of communication that is done village futsal kampung susuk medan and to know the influence of a strategy of communication with the resolution of the visit of consumers village futsal kampung susuk fields. This research using a method of quantitative with uses the technique of gathering data in the form of a questionnaire.Respondents in this study consisted of 100 people taken with the technique of non probability of sampling namely. accidental of sampling techniques who is found when gathering data and meet the criteria to be researched. Analysis of the results obtained the conclusion that a positive influence between a strategy of communication with the resolution of the visit of consumers in village futsal.A factor of a strategy of communication via the media advertising, publications, sales promotion, point of purchase communication, selling, personal and sponsorship marketing cause emotional stimuli and it brings consumer perceptions to produce a decision visit and use the facilities services are offered in village futsal. Research is also found a strategy of communication is directly proportional to the decision of the visit of consumers and based on the results of a correlation product moment it's got a conclusion that strategy of communication have a strong correlation to the decision of the visit of the consumer and has positive impacts which means that getting higher or gets better implementation of a strategy. Keywords: the strategy of communication, marketing, Village Futsal, The decision to visit, Consumers.